The Effect of Investment and Human Development Index on Economic Growth and Poverty Level in Balikpapan City - Istiqomah Istiqomah; Aji Sofyan Effendi; Muhammad Awaluddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the relationship and influence of independent variables, namely investment and human development index, intervening variables, namely economic growth with dependent variables, namely the poverty rate in Balikpapan city in 2010-2023. The tool used in this study is path analysis. The results of this study indicate that investment and HDI are positive and do not have a significant effect on economic growth. While on the poverty rate, investment and HDI variables directly have a significant but positive effect and economic growth variables are negative but do not provide a mediating effect on the relationship between investment and poverty rates and between HDI and poverty rates in Balikpapan city.